2004
DOI: 10.1073/pnas.0407645101
|View full text |Cite
|
Sign up to set email alerts
|

Harnessing phytochrome's glowing potential

Abstract: Directed evolution of a cyanobacterial phytochrome was undertaken to elucidate the structural basis of its light sensory activity by remodeling the chemical environment of its linear tetrapyrrole prosthetic group. In addition to identifying a small region of the apoprotein critical for maintaining phytochrome's native spectroscopic properties, our studies revealed a tyrosine-to-histidine mutation that transformed phytochrome into an intensely red fluorescent biliprotein. This tyrosine is conserved in all membe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
221
2
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 168 publications
(236 citation statements)
references
References 35 publications
12
221
2
1
Order By: Relevance
“…The hydrophobic contacts that the D-ring does make are primarily with conserved aromatic residues ( Figure 4A); these may provide rigidity to modulate the photochemical reaction. One of the residues lining the D-ring cavity, Tyr176, is known to be critical for proper photochemistry, perhaps by gating the rotation of the chromophore D-ring (Fischer and Lagarias, 2004). The photochemical gating role for this conserved Tyr residue in the bacteriophytochromes was more recently questioned .…”
Section: Light Sensing and Signal Transduction: New Insightsmentioning
confidence: 99%
See 1 more Smart Citation
“…The hydrophobic contacts that the D-ring does make are primarily with conserved aromatic residues ( Figure 4A); these may provide rigidity to modulate the photochemical reaction. One of the residues lining the D-ring cavity, Tyr176, is known to be critical for proper photochemistry, perhaps by gating the rotation of the chromophore D-ring (Fischer and Lagarias, 2004). The photochemical gating role for this conserved Tyr residue in the bacteriophytochromes was more recently questioned .…”
Section: Light Sensing and Signal Transduction: New Insightsmentioning
confidence: 99%
“…The P4 domain is however necessary both for efficient photochemistry and for the normal Pr spectrum, which are measures of bilin chromophore conformation (Falk, 1989). P4 therefore seems critical for optimizing the bilin chromophore environment to enable efficient photoconversion, perhaps by conferring rigidity to the bound bilin and thereby minimizing competing radiationless deexcitation pathways (Wu and Lagarias, 2000;Fischer and Lagarias, 2004). It was previously reported that P2 and P3 are related to domains known to be involved in ligand binding and signal transduction (Montgomery and Lagarias, 2002): P2 domains of some phytochrome protein sequences have been identified by domain database searches to be PAS domains (named for period clock, ARNT, and singleminded proteins; Ponting and Aravind, 1997), while P3 is identified as a GAF domain (named for vertebrate cGMP-specific phosphodiesterases, cyanobacterial adenylate cyclases, and the transcription activator FhlA; Aravind and Ponting, 1997).…”
mentioning
confidence: 99%
“…By using this technique, van Thor et al (9) determined that the formation of Lumi-R proceeded with 3-, 14-, and 134-ps time constants, but they were unable to assign which of the three temporal phases corresponded to Lumi-R formation. A 3-ps formation time constant for the Lumi-R ground state is inconsistent with the relatively highfluorescence quantum yield (Ϸ0.005) and the long excited-state lifetime (Ϸ30 ps) observed for the P r form of plant and cyanobacterial (Cph1) phytochromes (14,15). More recent time-resolved mid-IR work on the bacterial phytochrome Agp1 detected three time constants: 0.7 ps, consistent with the formation of the vibrationally excited ground state; 3 ps, reflecting ground-state cooling; and 33 ps, assigned to Lumi-R photoproduct formation (10).…”
mentioning
confidence: 92%
“…[5][6][7][8][9] There are several advantages of Phys 10 and CBCRs, 1 or domains thereof, that make them potentially interesting tools in biological analytics: they can be obtained by heterologous co-expression of protein-and chromophorecoding genes; and chromophore attachment is autocatalytic and does not require co-expression of lyases. 11 Their use as fluorescent biomarkers is impaired, however, by the relatively low fluorescence quantum yield.…”
Section: Introductionmentioning
confidence: 99%